Challenges in Transition of Care for Patients With Anorectal Malformations: A Systematic Review and Recommendations for Comprehensive Care. Issue 3 (March 2018) - Cairo, Sarah B.; Gasior, Alessandra; Rollins, Michael D.; Rothstein, David H.
Abstract : BACKGROUND: Anorectal malformations are one of the most common congenital intestinal anomalies affecting newborns. Despite advances in neonatal care and surgical techniques, many patients with a history of anorectal malformations are affected by long-term challenges involving bowel and bladder dysfunction, sexual dysfunction, and psychosocial issues. These outcomes or challenges are additionally exacerbated by the lack of a structured transition of care from the pediatric to the adult setting. OBJECTIVE: The purpose of this review is to describe the long-term outcomes affecting patients with a history of anorectal malformations, review the current literature on transition of care, and make recommendations for developing a standardized program for transitioning care for a select group of colorectal surgical patients. DATA SOURCES: An extensive PubMed review of articles in English was performed to evaluate current best practices for chronic illnesses of childhood with residual symptoms or need for medical care into adulthood. STUDY SELECTION: Meta-Analysis of Observational Studies in Epidemiology group guidelines were followed. MAIN OUTCOME MEASURES: The primary outcome for this review was the existence of transitional services for patients with a history of anorectal malformations and evaluations of long-term outcomes affecting patients with a history of anorectal malformations. RESULTS: Systematic review revealed improved results in transition programs as determined by patient follow-up, medication adherence, and patient and family satisfaction through the use of multidisciplinary teams. Standardized tools for assessing all aspects of patient outcomes and quality of life are essential for describing the burden of disease affecting a transitioning population. LIMITATIONS: This is a retrospective review of the current status of a complex and rapidly evolving field of delivery of care. More work is needed to apply uniform approaches and assess the impact, patient outcomes, and quality of life. CONCLUSIONS: Patients who undergo childhood procedures for anorectal malformations often experience chronic symptoms related to the bowel, bladder, and reproductive organs, as well as psychosocial disturbances. This population will benefit from appropriate engagement in transitional care plans. SeeVideo Abstract athttp://links.lww.com/DCR/A543 . Abstract : Supplemental Digital Content is available in the text.